2007
DOI: 10.1097/cad.0b013e3280115111
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide induces early and late apoptosis in human papilloma virus+ cervical cancer cells by inhibiting reactive oxygen species decay, diminishing the intracellular concentration of glutathione and increasing nuclear factor-κB translocation

Abstract: Ceramide is regarded as an important cellular signal for the induction of cell death. We have previously shown that ceramide induces the death of cervical tumor cells without biochemical and morphological markers of apoptosis. The mechanisms by which ceramide induces cell death are not understood, therefore we evaluated the effect of C6-ceramide, a synthetic cell-permeable analog of endogenous ceramides, in signaling pathways involved in the oxidative stress of three cervical human papilloma virus cancer cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…3C, bar graph), whereas the combination produced both supra-additive DNA fragmentation and caspase-3 activation and subsequent PARP cleavage. It is well known that natural ceramides activate pro-apoptotic events; the same has been demonstrated with short-chain ceramides [4143]. Interestingly, in a model of human keratinocytes, C6-ceramide exposure induced apoptosis via the salvage pathway [44], wherein C6-ceramide is hydrolyzed by ceramidase, and the liberated sphingosine reacylated by ceramide synthase to generate long-chain ceramides.…”
Section: Discussionmentioning
confidence: 97%
“…3C, bar graph), whereas the combination produced both supra-additive DNA fragmentation and caspase-3 activation and subsequent PARP cleavage. It is well known that natural ceramides activate pro-apoptotic events; the same has been demonstrated with short-chain ceramides [4143]. Interestingly, in a model of human keratinocytes, C6-ceramide exposure induced apoptosis via the salvage pathway [44], wherein C6-ceramide is hydrolyzed by ceramidase, and the liberated sphingosine reacylated by ceramide synthase to generate long-chain ceramides.…”
Section: Discussionmentioning
confidence: 97%
“…Phosphatidylcholine-specific PLC (PC-PLC), which is activated by t10,c12-CLA in adipocytes [48], has been shown to cause lysosomal destabilization [80]. This enzyme can also activate sphingomyelinase to promote the processing of sphingolipid into ceramide [81,82], a lipid messenger which has been shown to promote oxidative stress, induce ER stress and cause apoptosis [83-85]. Third , release of Ca 2+ from the ER promotes ER stress [86,87], and there is increasing evidence suggesting that ER stress can induce ROS formation [38,41,88], thus creating a vicious cycle since oxidative stress can induce ER stress [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously demonstrated that graphene oxide nanoparticles can act as anti‐oxidants and allow the buffering of reaction oxygen species (ROS) (Qiao, Zhang, Wang, Ma, & Su, ). ROS is an important cell signaling mechanism that has largely pro‐apoptotic effects, and has been shown to be an important mediator of both UV and C 6 ceramide induced apoptosis (Artyukhov, Trubitsyna, Nakvasina, & Solov'eva, ; Degli Esposti & McLennan, ; Gutierrez, Mendoza, Montano, & Lopez‐Marure, ; Valencia & Kochevar, ). In this case, we have demonstrated that O‐GNRs alone are capable of rescuing HeLa cells from the pro‐apoptotic stressors of UV irradiation and C 6 ceramide (Figures and ).…”
Section: Discussionmentioning
confidence: 99%